The long arc of justice : lesbian and gay marriage, equality, and rights - Mohr, Richard D. (Columbia University Press, 2005)
Engaging the whole spectrum of public-policy issues affecting gays and lesbians from a humanistic and philosophical approach, Richard Mohr uses the tools of his trade to assess the logic and ethics of gay rights. Focusing on ideas and values, Mohr's nuanced case for legal and social acceptance applies widely held ethical principles to various issues, including same-sex marriage, AIDS, and gays in the military. By drawing on cultural-, legal-, and ethical-based arguments, Mohr moves away from tired political rhetoric and reveals the important ways in which the struggle for gay rights an.